2004
DOI: 10.1038/sj.bjc.6601651
|View full text |Cite
|
Sign up to set email alerts
|

Parental cigarette smoking and childhood risks of hepatoblastoma: OSCC data

Abstract: Reported cigarette smoking habits for the parents of 43 UK children who died with hepatoblastoma (1953 -55 deaths, 1971 -81 deaths) have been compared with corresponding information for the parents of 5777 healthy control children by means of unconditional logistic regression. Hepatoblastoma risks were doubled if both parents smoked relative to neither parent smoking (RR 2.28, 95% CI 1.02 -5.09).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 13 publications
0
38
1
2
Order By: Relevance
“…An excess of maternal pre-eclampsia, without adjustment for VLBW, has been noted (Ansell et al, 2005). Three previous studies have found that maternal smoking significantly raised offspring risk (Pang et al, 2003;Sorahan and Lancashire, 2004;McLaughlin et al, 2006), whereas a fourth did not (Buckley et al, 1989); associations remained after adjustment for VLBW in two studies (Pang et al, 2003;Spector and Ross, 2003;McLaughlin et al, 2006). Lastly, a ninefold increased risk of hepatoblastoma was reported among children born following infertility treatment, which was independent of birth weight (McLaughlin et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…An excess of maternal pre-eclampsia, without adjustment for VLBW, has been noted (Ansell et al, 2005). Three previous studies have found that maternal smoking significantly raised offspring risk (Pang et al, 2003;Sorahan and Lancashire, 2004;McLaughlin et al, 2006), whereas a fourth did not (Buckley et al, 1989); associations remained after adjustment for VLBW in two studies (Pang et al, 2003;Spector and Ross, 2003;McLaughlin et al, 2006). Lastly, a ninefold increased risk of hepatoblastoma was reported among children born following infertility treatment, which was independent of birth weight (McLaughlin et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…The association with parental smoking was strongest (relative to neither parent smoking) when both parents smoked (OR,4.74;, P = 0.003). Sorahan & Lancashire (2004) found no increased risk associated with maternal or paternal smoking alone compared to nonsmokers, in both adjusted and unadjusted analyses. In contrast, parental smoking (paternal and maternal smoking combined) was strongly and consistently associated with an increased risk for hepatoblastoma in both adjusted and unadjusted analyses.…”
Section: (A) Parental Smoking Exposurementioning
confidence: 91%
“…Also, hepatoblastomas, like many other embryonal tumours, are associated with Beckwith-Wiedemann syndrome and hemihypertrophy, further suggesting a gestational oncogenic event (DeBaun & Tucker, 1998). Data were available for both maternal and paternal exposures from two studies Sorahan & Lancashire, 2004) while two other studies (McLaughlin et al, 2006;Pu et al, 2009) were limited to data on maternal smoking, available from birth certificates and medical records, respectively (Table 2.28). Most of these studies had limited sample sizes given the extreme rarity of these tumours.…”
Section: Hepatoblastomamentioning
confidence: 99%
See 2 more Smart Citations